1992
DOI: 10.1093/jat/16.5.311
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Cocaine and Metabolites in Plasma of Humans Following Intravenous Administration and Smoking of Cocaine

Abstract: Plasma was obtained from 10 human subjects at various intervals after administration of two rapid doses of cocaine, either intravenously or by smoking, and multiple doses by smoking and intravenously. The plasma was analyzed for COC and its metabolites, benzoylecgonine (BE) and ecgonine methyl ester (EME). Plasma concentrations of COC were found to be dose-dependent. For patients receiving two successive doses of COC intravenously (IV) or by smoking (SM), the average half-life of COC was found to be between 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
28
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 5 publications
6
28
0
3
Order By: Relevance
“…It is possible that women were not metabolizing cocaine as efficiently as men, and had we continued to measure plasma concentrations, benzoylecgonine plasma concentrations may have continued to rise in women as compared to men. To our knowledge, only one other study, conducted in men, measured cocaine and benzoylecgonine plasma concentrations after repeated doses of cocaine (Isenschmid et al 1992). They found that after the last cocaine dose, cocaine and benzoylecgonine plasma concentrations were similar to each other, which was also observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that women were not metabolizing cocaine as efficiently as men, and had we continued to measure plasma concentrations, benzoylecgonine plasma concentrations may have continued to rise in women as compared to men. To our knowledge, only one other study, conducted in men, measured cocaine and benzoylecgonine plasma concentrations after repeated doses of cocaine (Isenschmid et al 1992). They found that after the last cocaine dose, cocaine and benzoylecgonine plasma concentrations were similar to each other, which was also observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, in the elegant cocaine pharmacokinetic study by Mendelson et al (1999b) cocaine metabolite levels were not reported. Other studies in men have shown that BZE levels continue to rise approximately 75 min after the last cocaine dose (Isenschmid et al, 1992) and can remain elevated and relatively stable 1-6 h after a single i.v. dose of cocaine (Cone, 1995).…”
Section: Pharmacokinetics Of the Cocaine Metabolites Bze And Emementioning
confidence: 91%
“…A lthough cocaine binds only transiently to its receptors and is cleared rapidly from plasma (1,2), some of its effects persist after weeks or even months of abstinence (3)(4)(5). Persistence of effects could be caused by cellular mechanisms (6, 7) but also by direct chemical modification of proteins.…”
mentioning
confidence: 99%
“…Cocaine is cleared from plasma in humans through hydrolysis of its ester groups (2). Benzoyl ester hydrolysis is mediated by various enzymes, but significant hydrolysis of the methyl ester occurs spontaneously under physiologic conditions.…”
mentioning
confidence: 99%